A night in the lonesome October - Zelazny, Roger (Harper Voyager, 2025)
"Under cover of the murky London gloom, a knife-wielding gentleman named Jack prowls the midnight streets with his faithful watchdog Snuff--gathering together the grisly ingredients they will need for an upcoming ancient and unearthly rite. For soon, after the death of the moon, black magic will summon the Elder Gods back into the world. But Snuff and his master are not alone. All manner of participants, both human and not, are about with their ancient tools and their animal familiars in preparation for the dread night. It is brave, devoted Snuff who must calculate the patterns of the Game and keep track of the Players--the witch, the mad monk, the vengeful vicar, the Count who sleeps by day, the Good Doctor and the hulking Experiment Man he fashioned from human body parts, and a wild-card American named Larry Talbot--all the while keeping Things at bay and staying a leap ahead of the Great Detective, who knows quite a bit more than he lets on. Some have come to open the gates. Some have come to slam them shut. As the hour approaches--let the Game begin..."--Publisher website.